Drinking water delivery in the outer Torres Strait Islands: A case study addressing sustainable water issues in remote Indigenous communities. Issue 1 (2nd January 2021) - Hall, Nina L.; Grodecki, Heidi; Jackson, Greg; Go Sam, Carroll; Milligan, Brad; Blake, Chris; Veronese, Toni; Selvey, Linda
ABSTRACT: Safe drinking water provision in remote Australian Indigenous communities can raise many challenges. An initiative to enhance drinking water treatment was piloted in Australia's remote Torres Strait Islands. It was co-designed through close involvement of Torres Strait Islander local government officers and water operators. Data collection and analysis was undertaken independent researchers to assess the effectiveness of the pilot, drawing on both quantitative and qualitative sources, including field visits to the two Torres Strait Islands. The findings identified three key features for an effective programme of safe water delivery: appropriate infrastructure that is 'fit for purpose, place and people'; mentoring and technical support for remotely located water operators, and cooperation across relevant state and local government agencies. The pilot initiative has adaptive potential for other remote communities and for other basic services, including wastewater treatment and solid waste management.